Design in motion : film experiments at the Bauhaus - Frahm, Laura, 1978- (Leonardo (Series) (Cambridge, Mass.), 2022)
"Film by Design considers visual media, and particularly film, as a crucial link in the Bauhaus's visionary pursuit of integrating art and technology"--